OBSESSIVE COMPULSIVE DISORDER - Revathee Ramasamy; Wayan Westa; Nyoman Ratep (Bali Journal of Medical and Health Sciences, 2013)
Obsessive compulsive disorder (OCD) is an anxiety disorder characterized by intrusive thoughts that produce uneasiness, apprehension, fear, or worry, by repetitive behaviors aimed at reducing the associated anxiety, or by a combination of such obsessions and compulsions. OCD sufferers generally recognize their obsessions and compulsions as irrational, and may become further distressed by this realization. An Epidemiological Catchment Area (ECA) study showed a lifetime prevalence of OCD of 2.5%. Biological, psychological and psychosocial all play a role in causing the disorder. A diagnosis of OCD is drawn from its clinical presentations. The Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV- TR) is used to aid the diagnosis of OCD. Therapies for OCD are in the form of psychotherapy and psychopharmacology. OCD symptoms persist at moderate levels even following adequate treatment course and a completely symptom-free period is uncommon.